Analysis of Recruitment, Selection, and Placement on Employee Performance (Study on the West Papua Provincial Education Office) - Dowansiba, Barnabas (Green Publisher Indonesia, 2024)
Background: Human resources (HR) are an essential asset for every organization, including the West Papua Provincial Education Office, where effective recruitment, selection, and placement play a vital role in achieving optimal performance. High employee performance can drive the achievement of organizational goals, but many organizations face challenges in managing the proper recruitment and selection process, resulting in inappropriate employee placement. Purpose: This study aims to examine and analyze the influence of recruitment, selection, and placement on the performance of employees of the West Papua Provincial Education Office. Methods: This research method uses a quantitative method. The research sample consisted of 114 employees of the Papua Basrat Provincial Education Office. Data was collected using questionnaires and then processed using the SPSS program. Meanwhile, the data testing techniques used in this study include validity tests, reliability tests with Cronbach's Alpha, normality tests, multicollinearity tests, multiple linear regression analysis, t-tests, and determination coefficients. Results: The results showed that employee placement had a positive and significant influence on employee performance, selection had a positive and significant influence on employee performance, and recruitment did not have a significant influence on employee performance. Conclusion: Effective placement and selection are the primary keys to improving employee performance, while the recruitment process needs to be improved to achieve more optimal results.